2022
DOI: 10.1007/s11356-022-21125-w
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective to improve the treatment of Lianhuaqingwen on COVID-19 and prevent the environmental health risk of medication

Abstract: Lianhuaqingwen (LH), one traditional Chinese medicine (TCM), has been used to treat the coronavirus disease 2019 (COVID-19), but its ecotoxicity with potential human health security has not been well investigated. To overcome such adverse effects and improve its medication efficacy, an intelligent multi-method integrated dietary scheme, screening, and performance evaluation approach was developed. Thirteen LH compounds were selected, and the main protease (Mpro) was used as the potential drug target. Resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…However, the antiviral efficacy of polyphenols including lignans and plant sterols has been confirmed against SARS-CoV, MERS-CoV, Ebola virus, HIV, influenza virus and other viruses causing respiratory tract infections (18)(19)(20)(21). Recent studies have also demonstrated their beneficial effects against the SARS-CoV-2 virus (18,(22)(23)(24) resulting from their ability to bind to peak protein sites on the ACE2 receptor used by SARS-CoV-2 to infect cells (25, 26), regulate ACE2 expression and also interfere with SARS-CoV-2 replication by inhibiting the virus protease or inhibiting SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) (27,28). The antiviral activity of some of them is comparable to or stronger than pharmacological agents (naringenin, vs. remdesivir (29), citrus flavonoids and polyphenols from Curcuma spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the antiviral efficacy of polyphenols including lignans and plant sterols has been confirmed against SARS-CoV, MERS-CoV, Ebola virus, HIV, influenza virus and other viruses causing respiratory tract infections (18)(19)(20)(21). Recent studies have also demonstrated their beneficial effects against the SARS-CoV-2 virus (18,(22)(23)(24) resulting from their ability to bind to peak protein sites on the ACE2 receptor used by SARS-CoV-2 to infect cells (25, 26), regulate ACE2 expression and also interfere with SARS-CoV-2 replication by inhibiting the virus protease or inhibiting SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) (27,28). The antiviral activity of some of them is comparable to or stronger than pharmacological agents (naringenin, vs. remdesivir (29), citrus flavonoids and polyphenols from Curcuma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory storm is a systemic inflammatory response triggered by various factors, including infection and drugs, and is characterized by a sharp increase in the levels of a large number of pro-inflammatory cytokines. Evidence from a wide range of sources suggests that SARS-CoV-2 infection induces an excessive inflammatory response and cytokine storm (CS), and CS is a vital factor in the conversion of patients with COVID-19 from mild to severe and critical illness (Gu et al, 2022). After infection with SARS-COV-2, the innate immune system is triggered, and various inflammatory pathways are activated, among which NLRP/IL-1β, JAK/STAT, TNF-α/NF-κB, and other pathways have been confirmed to be closely related to SARS-CoV-2 infection (Jiang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lianhua Qingwen, a Chinese patent medicine containing L. japonica , has good antiviral, immunomodulatory, and anti-inflammatory activities. It has been prescribed for the prevention and treatment of coronavirus infections [ 98 ]. According to the performance report of Lianhua Qingwen’s manufacturer Yiling Pharmaceutical, in 2022, it is expected to achieve net profit of CNY 21.5 to 24.19 billion, an increase of 60% to 80% over the same period last year, and its highest net profit has been close to the sum of 2020 and 2021.…”
Section: Practical and Potential Applications Of L Japonica...mentioning
confidence: 99%